The impact of late follicular progesterone level on in vitro fertilization-intracytoplasmic sperm injection outcome: Case-control study - Diana Novia; Hilma Putri Lubis; Binarwan Halim; Anantya Pustimbara; Retno Lestari; Abinawanto Abinawanto; Anom Bowolaksono (Shahid Sadoughi University of Medical Sciences, 2020)
Background: Studies have been conducted to improve the pregnancy rate through the in vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) program. In recent years, researchers have been focusing on finding impact of high progesterone level on endometrial receptivity. However, data on whether progesterone level also affects the quality of the embryo is still limited. Objective: The aim is to assess the effect of late follicular progesterone level on the outcome of in vitro fertilization-intracytoplasmic sperm injection (IVF-ICSI). Materials and Methods: This was a case-control of 245 women who underwent in vitro fertilization cycle at Halim Fertility Center, Indonesia. The outcomes assessed were number of oocytes retrieved (OR), maturation rate (MR), fertilization rate (FR), number of good embryos (GE), number of fair embryos (FE), and number of poor embryos (PE). The progesterone (P4) and estradiol (E2) levels were analyzed on the day of human chorionic gonadotropin injection. Serum progesterone level was divided into three groups: 1. low progesterone ( ≤ 0.50 ng/ml), 2. normal progesterone (0.51-1.50 ng/ml), and 3. high progesterone ( > 1.50 ng/ml). All outcomes were compared amongst the groups. Results: Significant differences occurred between progesterone level on the day of human chorionic gonadotropin administration. The number of OR in group 1, 2, and 3 were 8.41 ± 5.88 vs. 12.99 ± 8.51 vs. 17.58 ± 9.52, respectively. Conclusion: Progesterone level on the day of human chorionic gonadotropin injection may have an impact on the outcome of IVF-ICSI.